2017
DOI: 10.1007/s00167-017-4605-8
|View full text |Cite
|
Sign up to set email alerts
|

Biophysical stimulation improves clinical results of matrix-assisted autologous chondrocyte implantation in the treatment of chondral lesions of the knee

Abstract: II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…H&E staining of the graft‐host junction was more intense in PEMF‐treated repairs (Figure 6e,f). It is possible that these modest beneficial results at 3 months may be strengthened with increased duration of PEMF stimulation, as clinical studies of cartilage restoration typically follow‐up for 2 years or longer (Collarile et al, 2018; Osti et al, 2015). It is also possible that a less robust effect was observed in OCA subscores due to minor variations in PEMF orientation introduced by knee flexion and repair location (TG vs. FCL or FCM).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…H&E staining of the graft‐host junction was more intense in PEMF‐treated repairs (Figure 6e,f). It is possible that these modest beneficial results at 3 months may be strengthened with increased duration of PEMF stimulation, as clinical studies of cartilage restoration typically follow‐up for 2 years or longer (Collarile et al, 2018; Osti et al, 2015). It is also possible that a less robust effect was observed in OCA subscores due to minor variations in PEMF orientation introduced by knee flexion and repair location (TG vs. FCL or FCM).…”
Section: Discussionmentioning
confidence: 99%
“…Historically, PEMFs have been used in a clinical setting to treat delayed unions of bone fractures (Becker, Spadaro, & Marino, 1977). More recently, clinical studies of PEMFs have shown improvements in subjective measures of clinical function and pain following anterior cruciate ligament (ACL) reconstruction, bone marrow–derived stem cell transplantation, matrix‐assisted chondrocyte implantation (MACI®), microfracture, and chondroabrasion (Benazzo, Zanon, et al, 2008; Cadossi et al, 2014; Collarile, Sambri, Lullini, Cadossi, & Zorzi, 2018; Osti, Del Buono, & Maffulli, 2015; Zorzi, Dall'Oca, Cadossi, & Setti, 2007). However, while these initial clinical studies were promising, additional preclinical and mechanistic studies are required to support or oppose the regular use of PEMFs as an adjuvant strategy for cartilage repair rather than as a pain management tool (American Academy of Orthopaedic Surgeons Board of Directors, 2013; Bjordal et al, 2007; Gobbi, Lad, Petrera, & Karnatzikos, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pulsed signal therapy (PST) is an extension of pulsed electromagnetic field therapy (PEMF) consisting in a patented pulse frequency for bones and soft tissue (PST MOBIL, Bio Magnetic Therapy Systems, Munich, Germany). PST has been used empirically to treat various diseases, including arthrosis of various joints, spine pain syndromes, tendinopathy, sports injuries, and even as an adjunct in rheumatic diseases [Moretti et al, ; Massari et al, ; Collarile et al, ].…”
Section: Introductionmentioning
confidence: 99%